KAJIAN POTENSI MATAAIR DI KAWASAN KARST, GUNUNGKIDUL: (Kasus : Kecamatan Panggang - , ADHITYO HARYADI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Springs that are found in Gunungkidul karst region is potential water resources that canât be ignored. Springs in this region have different character of quantity and quality because of its specific morphology and lithology. A lot of resident in arid region like Gunungkidul, are enact spring as one of fount to meet their needs. So, it is necessary to do a study to know the character of quantity and quality of springs in karst region at Gunungkidul, springs distribution, and its potential to fulfill water needs of resident in the future. Survey method is dominant in this research. Purposive sampling method used to springs sampling which are taken to laboratory testing and respondent sampling which are be interviewed. The research is descriptive and comparative. Descriptive analysis is used to describe the condition and characteristic of springs. Comparative analysis is used to compare and classify physical and chemical feature of springs from the result of laboratory test. Projection is performed to determine how long springs quantity can fulfill water needs. At last, this research resulted that the springs in Panggang District are unevenly distributed, 6 of 11 springs are located at Girisuko, and the others spreads in Giriharjo, Giriwungu and Girikarto. Type of springs in Panggang District is contact, emergence and exsurgence. In quantity, daily discharge reach out total 20,319.9 m3 that potentially can be able to fulfill Panggang Districtâs resident water needs until 2028. In quality, water of springs dominate by high element of calcium (Ca2+) (170 â 108 mg/L), magnesium (Mg2+) (5 â 53 mg/L), and hardness (CaCO3) (200 â 435 mg/L). The height of the element (calcium, magnesium and hardness) can be tolerated by treatments that is deposit its element before consumed. Keyword : springs, karst, water supply, springs ability